Barriers to RFID Adoption in Material Management of Construction Industry: The Perception of Project Manager - Chen, Xiao Wen; Nurul Aini, Osman* (INTI International University, 2020)
Technology has become more sophisticated to deliver comfort in daily life. A merging with enormous and gigantic building projects could create a greater output. In this paper, the Radio Frequency Identification (RFID) implementation will show in a few aspects improvisation for materials management in a construction project. However, in Malaysia construction industry, the implementation of RFID is seen as shallow and stagnant. The benefits of implementing RFID technology in material management have been discussed since the construction players in Malaysia are still mostly unaware of its potential. As a project manager in construction projects, it is vital to evaluate their understanding, as they are the top-level management on the construction project. A holistic questionnaire were used as the tool for gathering the interpretation from construction industry project managers. The findings show that for the construction project, most project managers are aware of the RFID technology but have very less understanding of assimilation into material management. It also revealed that most construction companies were hesitant to use this technology because of high costs and fewer experts to manage the technology.